1999
DOI: 10.1007/s004220050516
|View full text |Cite
|
Sign up to set email alerts
|

Distortions of length perception

Abstract: A combined influence of stimulus orientation and structure on the judgment of length was tested in psychophysiological experiments. The subjects adjusted the test part of a stimulus to be equal in length to the reference part. The orientation of the parts of the stimulus varied in the experiments. The stimuli (three dots or the Oppel-Kundt figure, which had ten dots within the filled part) were generated on the monitor. In the Oppel-Kundt figure, the filled part was considered as a reference and the empty part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
0
21
0
Order By: Relevance
“…In our previous seeking of underlying principles behind the misperception of extent (Bulatov et al 1997, Bulatov and Bertulis 1999, the main attention was drawn to the cortical processes of spatial-frequency filtering. Since the computational procedures of the current model represent some calculations of convolution and spatial integration, it can be considered as a further development of the "filtering" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous seeking of underlying principles behind the misperception of extent (Bulatov et al 1997, Bulatov and Bertulis 1999, the main attention was drawn to the cortical processes of spatial-frequency filtering. Since the computational procedures of the current model represent some calculations of convolution and spatial integration, it can be considered as a further development of the "filtering" hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…According to the "contour density" hypothesis (Craven andWatt 1989, Watt 1990), the number of zero-crossings of the spatial profile of neural excitation caused by the filled part of the Oppel-Kundt figure can be one of the most important factors determining the illusion magnitude. A rather adequate description of illusory effects was obtained from the computational model seeking to explain the misperception of extent in terms of physiological (i.e., based on the spatial properties of the receptive fields of neurons in the primary visual cortex) spatial-frequency filtering (Bulatov et al 1997, Bulatov and Bertulis 1999, as well as from the quantitative approach that explains the illusion occurrence by internal noises in the neural networks (Fermüller and Malm 2004).…”
Section: Introductionmentioning
confidence: 99%
“…This illusion has been widely studied, both in two-(e.g. Bulatov and Bertulis 1999;Bulatov et al 1997;Coren and Girgus 1978;Giora and Gori 2010) and three-dimensional space (Deregowsky and McGeorge 2006). It has been found that its strength varies as a function of several characteristics of the stimulus, such as size, orientation and the number of Wlling lines (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…It has been found that its strength varies as a function of several characteristics of the stimulus, such as size, orientation and the number of Wlling lines (e.g. Bulatov and Bertulis 1999;Bulatov et al 1997;Coren and Girgus 1978) and, more generally, of the textural statistical properties of the visual object (Giora and Gori 2010). Importantly, the OKI consistently produced a distortion of space orthogonal to the Wlling lines' orientation: that is, when vertical lines are presented, the space is overestimated along its horizontal extent.…”
Section: Introductionmentioning
confidence: 99%
“…This fact may be explained by meridional anisotropy of the visual field, detected by numerous tests [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23], and sophisticated processes at higher levels of the visual system [8]. In addition, sensitivity to orientation may be determined by the perception of the direction of gravity [1,24].…”
mentioning
confidence: 99%